Martin Buber, His Intellectual and Scholarly Legacy. - Sam Berrin Shonkoff (Editor) (Religious Studies, Theology and Philosophy E-Books Online, Collection 2018, ISBN: 9789004353350., 2018)
Martin Buber: His Intellectual and Scholarly Legacy is a collection of contemporary reflections on one of the most pivotal figures of modern Jewish thought. Born in Austria and reared in Galicia, Buber (1878-1965) became a spiritual representative of Judaism in German culture before emigrating to Jerusalem on the brink of the Shoah. His prolific writings on matters spanning the Hebrew Bible and New Testament to Hasidism and Zionism inspired diverse audiences throughout the world. In this volume, Sam Berrin Shonkoff has curated an illuminating array of essays on Buber's thought by leading intellectuals from five different countries. Their treatments of Buber's dialogues with Christianity, politics, philosophy, and Judaism exhibit Buber's ramified legacy and will surely stimulate fruitful discussion in our own time.